The spleen-strengthening and liver-draining herbal formula treatment of non-alcoholic fatty liver disease by regulation of intestinal flora in clinical trial - Dengcheng Hui; Dengcheng Hui; Dengcheng Hui; Lu Liu; Lu Liu; Lu Liu; Nisma Lena Bahaji Azami; Nisma Lena Bahaji Azami; Nisma Lena Bahaji Azami; Jingru Song; Yanping Huang; Wan Xu; et al. (Frontiers in Endocrinology, 2023)
ObjectiveAs a metabolic disease, one important feature of non-alcoholic fatty liver disease (NAFLD) is the disturbance of the intestinal flora. Spleen-strengthening and liver-draining formula (SLF) is a formula formed according to the theory of “One Qi Circulation” (Qing Dynasty, 1749) of Traditional Chinese Medicine (TCM), which has shown significant therapeutic effect in patients with NAFLD in a preliminary clinical observation. In this study, we aim to explore the mechanism of SLF against NAFLD, especially its effect on glucolipid metabolism, from the perspective of intestinal flora.MethodsA prospective, randomized, controlled clinical study was designed to observe the efficacy and safety of SLF in the treatment of NAFLD. The study participants were randomly and evenly divided into control group and treatment group (SLF group). The control group made lifestyle adjustments, while the SLF group was treated with SLF on top of the control group. Both groups were participated in the study for 12 consecutive weeks. Furthermore, the feces of the two groups were collected before and after treatment. The intestinal flora of each group and healthy control (HC) were detected utilizing 16S rRNA gene sequencing.ResultsCompared with the control group, the SLF group showed significant improvements in liver function, controlled attenuation parameter (CAP), and liver stiffness measurement (LSM), meanwhile, patients had significantly lower lipid and homeostasis model assessment of insulin resistance (HOMA-IR) with better security. Intestinal flora 16S rRNA gene sequencing results indicated reduced flora diversity and altered species abundance in patients with NAFLD. At the phylum level, Desulfobacterota levels were reduced. Although Firmicutes and Bacteroidetes did not differ significantly between HC and NAFLD, when grouped by alanine transaminase (ALT) and aspartate transaminase (AST) levels in NAFLD, Firmicutes levels were significantly higher in patients with ALT or AST abnormalities, while Bacteroidetes was significantly lower. Clinical correlation analysis showed that Firmicutes positively correlated with gender, age, ALT, AST, LSM, and Fibroscan-AST (FAST) score, while the opposite was true for Bacteroidetes. At the genus level, the levels of Alistipes, Bilophila, Butyricimonas, Coprococcus, Lachnospiraceae_NK4A136 group Phascolarctobacterium, Ruminococcus, UCG-002, and UCG-003 were reduced, whereas abundance of Tyzzerella increased. There was no statistically significant difference in Firmicutes and Bacteroidota levels in the SLF group before and after treatment, but both bacteria tended to retrace. At the genus level, Coprococcus (Lachnospiraceae family), Lachnospiraceae_NK4A136 group (Lachnospiraceae family), and Ruminococcus (Ruminococcaceae family) were significantly higher in the SLF group after treatment, and there was also a tendency for Bilophila (Desulfovibrionaceae family) to be back-regulated toward HC.ConclusionsSLF can improve liver function and glucolipid metabolism in patients with NAFLD and lower down liver fat content to some extent. SLF could be carried out by regulating the disturbance of intestinal flora, especially Coprococcus, Lachnospiraceae_NK4A136 group, and Ruminococcus genus.